ETNOMATEMATIKA DAN NILAI KARAKTER DALAM PERMAINAN TRADISIONAL KEBETUK - Yuliana Olga Siba Sabon; Nur Hidayanto Pancoro Setyo Putro; Abdul Rahim (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
Traditional games are one of the cultural wealth in Indonesia. Along with the times and modernization, some traditional games are getting less and less attractive despite their national character values and benefits in increasing children's potential. To prevent the disappearance from society, they need to be preserved. One of the ways is by applying them in the learning process as has been implemented in several previous studies. However, from those studies, the researchers saw that many types of traditional games have still not been developed and applied in learning regardless of various types of educational traditional games. One example of a traditional game that has not been exposed is kebetuk, the one originating from the East Nusa Tenggara region, especially East Flores Regency. Therefore, the purpose of this research was to find out the mathematical elements and character values contained in Kebetuk. This research was conducted by discovering the concept of mathematics in culture (kebetuk game) which can be referred to as ethnomathematics. This research was qualitative research using the ethnographic method. The data collection process was carried out employing observation and in-depth interviews. From the results, it is known that the mathematical elements in the kebetuk game consist of the characteristics of the integer arithmetic operation principle (commutative, associative, distributive addition), pattern, combination, permutation, and probability. In addition, the character values contained the game are consensus, discipline, honesty, determination, and mutual cooperation. The kebetuk game can be applied in learning mathematics.